Effect Of Umbilical Cord Care Using the Topical Breastfeeding Method on The Length of Time for Releasing the Umbilical Cord of Newborns - Lely, Andi Nurlaily; Rusnawati; Risnawati (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2025)
Neonatal tetanus can occur, one of which is due to infection in the baby's umbilical cord, the faster the umbilical cord is released, reducing the risk of infection. Umbilical cord care using breast milk is the newest cord care which is cleaned and cared for by applying breast milk to the base of the umbilical cord using a cotton bud. This research designPre-Experiment with a static group comparison research design. The population of this study were newborns aged 0-8 days in the September-October period in the working area of the Bontobangun Health Center. The sample of this study were newborns aged 0 days as many as 24 babies with total sampling technique, which were divided into two intervention groups, namely the topical method of breast milk and the group of wrapping breast milk with dry gauze. Data analysis used the Chi Square test. The results of the Bivariate Analysis obtained a value of p = 0.000. This value is smaller than the value α = 0.05, so it can be concluded that 0.000 <0.05, so there is a significant effect between cord care using the topical breastfeeding method on the time of releasing the umbilical cord of newborns in the Working Area of the Bontobangun Health Center. The conclusion in this study is that treatment using the topical method of breast milk releases the umbilical cord faster than normal umbilical cord care. So that treatment using the topical method of ASI is more recommended Keywords; umbilical cord; topical breast milk